Non-HDL cholesterol levels in childhood and carotid intima-media thickness in adulthood - Juonala, M; Wu, F; Sinaiko, A; Woo, JG; Urbina, EM; Jacobs, D; Steinberger, J; Prineas, R; Koskinen, J; Sabin, MA; Burgner, DP; Burns, TL; et al. (American Academy of Pediatrics, 2020)
BACKGROUND: Elevated non–high-density lipoprotein cholesterol (HDL-C) levels are used to identify children at increased cardiovascular risk, but the use of non–HDL-C in childhood to predict atherosclerosis is unclear. We examined whether the National Heart, Lung, and Blood Institute classification of youth non–HDL-C status predicts high common carotid artery intima-media thickness in adulthood.